2015
DOI: 10.14202/vetworld.2015.970-976
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite based genetic diversity study in indigenous chicken ecotypes of Karnataka

Abstract: Aim:The current study was the first of its kind taken upon indigenous ecotypes of the Karnataka in order to unravel the diversity details at 20 chicken microsatellite regions.Materials and Methods:210 indigenous chicken belonging to six districts of Bangalore and Mysore division formed the target sample for the present study. The genomic deoxyribonucleic acid was isolated by phenol chloroform isoamyl alcohol method. A panel of 20 microsatellite regions, including 14 recommended by FAO and six identified from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Comparing to the present results on Ho and He , Rudresh et al [ 29 ] reported higher values (0.69 to 0.86) in two chicken populations of Karnataka, India while lower estimates (0.44 to 0.58) were found in Thai and Bhutanese native chickens [ 7 ]. It is notable to mention that direct comparison of data from different studies is probably difficult due to the different genetic backgrounds of the chicken populations studied and the different MS markers used [ 26 ].…”
Section: Resultscontrasting
confidence: 80%
“…Comparing to the present results on Ho and He , Rudresh et al [ 29 ] reported higher values (0.69 to 0.86) in two chicken populations of Karnataka, India while lower estimates (0.44 to 0.58) were found in Thai and Bhutanese native chickens [ 7 ]. It is notable to mention that direct comparison of data from different studies is probably difficult due to the different genetic backgrounds of the chicken populations studied and the different MS markers used [ 26 ].…”
Section: Resultscontrasting
confidence: 80%
“…Values ranging from 0.00 to 0.05 is considered as slight, 0.05 to 0.15 moderate, 0.15 to 0.25 is strong, and >0.25 is very strong genetic differentiation (Balloux & Lugon-Moulin, 2002). As a matter of fact, the expectation of F ST under complete differentiation will not always be one, so it might be not dealing with all real population differentiation (Rudresh et al, 2015). Therefore, an F ST value as low as 0.05 might reflect substantial genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we selected 37 and 32 microsatellite loci with good polymorphism in the outbred groups and haplotypes of chicken, respectively [ 12 , 16 , 17 ]. In addition, 15 and 23 loci were screened in the outbred groups and haplotypes of duck, respectively [ 14 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%